2021
DOI: 10.21203/rs.3.rs-975577/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Staging 68Ga-PSMA PET/CT in 963 Consecutive Patients with Newly Diagnosed Prostate Cancer: Incidence and Characterization of Skeletal Involvement

Abstract: Purpose: The aim of the study was to elaborate the incidence and type of skeletal involvement in a large cohort of patients with newly diagnosed prostate cancer (PCa) referred for Ga-68 PSMA-11 PET/CT staging in a single center.Methods: Study cohort included 963 consecutive patients with newly diagnosed PCa referred Ga-68 PSMA-11 PET/CT study for staging. The incidence of bone involvement, type of bone metastases, extent of disease were determined and correlated with the ISUP Grade Group (GG) criteria, and PSA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…In clinical practice, the [ 99m Tc]Tc-methylene diphosphonate bone scan has been conventionally employed for bone metastasis detection. Among the 52 patients who underwent bone scans, our study results indicate that [ 99m Tc]Tc-HYNIC-ALUG SPECT/CT is superior to bone scintigraphy in detecting bone metastases, as it can identify both bone marrow involvement and osteolytic metastases, consistent with previous findings from [ 68 Ga]Ga-PSMA-11 PET/CT (30). Otherwise, our study reported an 18% detection rate of bone metastasis in PCa patients with a PSA level of <20 ng/mL, which is significantly higher than the 4.7% detection rate observed in a previous study of 857 consecutive PCa patients (31).…”
Section: Discussionsupporting
confidence: 87%
“…In clinical practice, the [ 99m Tc]Tc-methylene diphosphonate bone scan has been conventionally employed for bone metastasis detection. Among the 52 patients who underwent bone scans, our study results indicate that [ 99m Tc]Tc-HYNIC-ALUG SPECT/CT is superior to bone scintigraphy in detecting bone metastases, as it can identify both bone marrow involvement and osteolytic metastases, consistent with previous findings from [ 68 Ga]Ga-PSMA-11 PET/CT (30). Otherwise, our study reported an 18% detection rate of bone metastasis in PCa patients with a PSA level of <20 ng/mL, which is significantly higher than the 4.7% detection rate observed in a previous study of 857 consecutive PCa patients (31).…”
Section: Discussionsupporting
confidence: 87%